PENGARUH HARGA, PENDAPATAN, DAN KUALITAS PELAYANAN TERHADAP PERMINTAAN PRODUK RESTORAN SUNDA DI WILAYAH BANDUNG - Rena Yulianti, - (2009)
This research is aim to know how big price influence, income and service quality to request of sundanese restaurant at Bandung. This research use analytic descriptive method and also use accidental sampling technique. In the sampling technique, this research use amount of 13 samples Sundanese restaurant at Bandung which has 92 people as respondents. For data analyse, this research use multiple linear regression. The Result of this research show that simultaneously of price, income, and service quality are influence to request of sundanese restaurant product at Bandung equal to 73,7% and 26,3% are influenced by other factor. Partially, price variable has the negative influence that is equal to (- 23,4%), income variable has the positive influence that is equal to 52%, and variable of service quality has the positive influence also that is equal to 99,3%.